Methodology of Teaching the Subject of Parameter Repetition Operator (In the example of the Python programming language) (Eurasian Journal of Research, Development and Innovation, 2022)
The article outlines methods of teaching a parameter repeat operator in teaching programming languages based on interfaith methods in the example of python programming language